HUBUNGAN PERTAMBAHAN BERAT BADAN IBU SAAT HAMIL BERDASARKAN INDEKS MASSA TUBUH DENGAN BERAT BADAN BAYI BARU LAHIR - Susilojati, Rr.Dewi; Akbid Estu Utomo Boyolali, Sri Handayani (Jurnal Kebidanan, 1970)
ABSTRACT The development of children from the fetus is determined from the nutritional quality of the mother, because all the nutritional intake of children from the mother. Nutritional status of pregnant women is less, at risk of having a baby Babies Low Birth Weight infant. Anthropometric examination can be used to determine the nutritional status of pregnant women for example by measuring the weight before pregnancy, height, body mass index (BMI). Knowing to look at the relationship between maternal weight gain during pregnancy based on the IMT-weight newborns. This type of study is a retrospective analytical approach. Population in the study were all post-partum mothers and newborns are recorded into the patient in Harmony RB Ambarawa from January to April 2012, amounting to 108 people. The tools used in the form of patient medical records. Most mother have normal weight, there are 52 respondents (61,2%) and most newborn have normal birth weight, there are 72 babies (84,7%) The results of Kendall-Tau correlation analysis with SPSS 18.0 program is the count Ï„ = (0399)> table Ï„ = (0.185) and the probability of Ï 00001 <Î¬ = 0.05, then Ho is rejected. Based on the result showed that there is a corresponding weight gain of maternal BMI with neonatal body weight. This suggests that the higher the weight of the normal maternal BMI was normal in the newborn's weight. Key words: normal maternal weight gain according to BMI, body weight of newborns.